Comparison between Tropical Rainfall Measuring Mission (TRMM) and Global Precipitation Measurement (GPM) Satelliteâs Rainfall Data for Study of Flood at Porong - Aji Pratama, Setya
Porong is region with high importance for East Java’s economy, thus flood that disturb transportation in the region will have big economic impact. Study of flood is done by comparing satellite’s rainfall data with flood event in Porong. Before analysis on flood can be done, rainfall data from Tropical Rainfall Measurement Mission (TRMM) and Global Precipitation Measurement (GPM) are analyzed statistically. GPM has R2 value of 0.82, better than TRMM’s 0.71. GPM has 0.88 for POD, 0.45 for FAR, and 0.51 for CSI, all of which are better than TRMM which has 0.84 for POD, 0.49 for FAR, and 0.46 for CSI. To do study on flood, a flood database is build using news from mass media between year 2009-2018 as sources. There 6 flood events gathered from this process, between year 2014-2018. From those 6 flood events, flood analysis using GPM’s data is done on 5 flood events that happened between March 2014-March 2018. The result shows that all flood events are preceded by rain events. 67% of preceeding rains have long-term pattern. Total rainfall affects how vast the flooded area is and how high the inundation is, with higher total rainfall means higher inundation and more area that got flooded. Other factors than impact the flood’s characteristic in Porong are elevation of Siring Sub-district and Pamotan village that are lower than surrounding area, and Ketapang River overflowing during flood events.